Technical Assessment of Industrial Solid Waste Recycling Process Based on the Willingness-to-Pay LCIA Model. (March 2019) - Guo, Huiting; Yang, Shuo; Wang, Xiuteng; Liu, Jing
Abstract: The recycle and reuse of solid waste must consider both the economic and environmental respect. For most of the present environmental technologies, the biggest obstacle for their practical implementation is the economic barrier. For some cases, even the technical process demonstrates the good performance in energy-saving, emission-reduction etc., but it is still hard to be applied due to the high operating cost. For most of the technology assessment and comparison, they are carried out only from the environmental or the economic perspective, and rarely combine the two respects. For assessing the recycle and reuse of solid waste in a more comprehensive manner, the present paper adopted the monetized LCIA method based on the Willingness-to-Pay theory. Based on the proposed method, a LCIA case study on the production process of sintered brick with coal fly ash was carried out. Through monetizing the environmental impact during its production process, it was found that the environmental cost resulted from the production of sintered brick is 8.76E-3Yuan/kg, namely, 8.76 Yuan/ton. The major environmental impact category is global warming, followed by the acidification and suspended particulate matter. In contrast, due to the reuse of industrial wastes as raw materials, the consumption of natural resources only accounts for a minor part of the entire environmental impacts. Therefore, the control of GHG emissions shall be prioritized for the technical optimization.